83 Trip Versus Slip: Implication of the Triggers of Falls on Physiological Fall Risk. (20th December 2019) - Lam, Freddy M H; Choy, Dicky T K; Leung, Jason C S; Kwok, Timothy C Y
Abstract: Introduction: Early identification of fallers with intrinsic fall risk factors could facilitate the delivery of timely and appropriate treatment. This study aims to see if the two most common triggers of falls – trip and slip, have an implication on the physiological profile of older fallers. Methods: One thousand one hundred and forty-one community-dwelling older adults aged 60 years or above who had a fall in the past year were recruited in Hong Kong. Details on the falls experienced by the elderly were recorded in an interview. Physiological fall risk of the participants was measured by the short-form Physiological Profile Assessment (PPA). It assesses vision, reaction time, proprioception, balance, and knee extension strength. Mobility was assessed by the 10-meter walk test at comfortable speed. Analysis of Co-variance (ANCOVA) was used to compare the assessment results between those who only experienced trip and falls (n=378; 316 female; mean age=70.4±7.2) and those who only experienced slip and falls (n=204; 159 female; mean age=70.1±7.1) while adjusting for gender proportion. Chi-square test was used to evaluate the difference in the proportion of recurrent fallers across groups. Results: Elderly who experienced only trip and falls have a significantly lower knee extension strength (22.9±8.3kg) compare with those who experienced only slip and falls (25.0±9.18 kg; p=0.031). They also tend to take longer to complete the 10-meter walk test (Trip only: 10.17±2.88; Slip only: 9.72±2.63; p=0.085). A higher percentage of those who tripped were recurrent fallers but the difference was insignificant (Trip only: 11.6%; Slip only: 8.3%; p=0.214). No other outcome measure was found to be significantly different across groups (p≥0.418). Conclusion: Elderly who tripped and fell have worse physical ability than those who slipped. They are potentially better candidates for fall prevention exercise intervention.